Can Authority be Sustained while Balancing Accessibility and Formality? - Hashimzade, Nigar; Myles, Georgina A.; Myles, Gareth D. (HERMES - Journal of Language and Communication in Business, 2014)
Economics has developed into a quantitative discipline that makes extensive use of mathematical and statistical concepts. When writing a dictionary for economics undergraduates it has to be recognised that many users will not have sufficient training in mathematics to benefi t from formal definitions of mathematical and statistical concepts. In fact, it is more than likely that the user will want the dictionary to provide an accessible version of a definition that avoids mathematical notation. Providing a verbal description of a mathematical concept has the risk that the outcome is both verbose (compared to a definition using appropriate mathematical symbols) and imprecise. For the author of a dictionary this raises the question of how to resolve this conflict between accessibility and formal correctness. We use a range of examples from the Oxford Dictionary of Economics to illustrate this conflict and to assess the extent to which a non-formal definition can be viewed as authoritative.